THE URAL NORTH: EVOLUTION OF STUDYING AND ECONOMIC DEVELOPMENT - V.P. Pahomov; V.G. Loginov (Экономика региона, 2007)
The process of evolution of studying and economic development of the Ural North, the territory having significant perspective in-resource potential is considered in clause. The basic attention is given to becoming of socio-economic researches on studying natural resources of Northern, Subpolar and Polar Ural for definition of an opportunity of their using in facilities of industrial Ural.